Transcranial magnetic stimulation improves cognition over time in Parkinson's disease. (September 2019) - Trung, Jessica; Hanganu, Alexandru; Jobert, Stevan; Degroot, Clotilde; Mejia-Constain, Beatriz; Kibreab, Mekale; Bruneau, Marie-Andrée; Lafontaine, Anne-Louise; Strafella, Antonio; Monchi, Oury
Abstract: Introduction: Cognitive impairment can occur in the early phase of Parkinson's disease and increases the risk of developing dementia. Cognitive deficits were shown to be associated with functional alterations in the dorsolateral prefrontal cortex (DLPFC) and caudate nucleus. Two previous transcranial magnetic stimulation studies over the left DLPFC showed short-term improvement in cognitive performance and focused on specific task. Methods: 28 patients with idiopathic Parkinson's disease and mild cognitive impairment received intermittent "theta burst" stimulation (iTBS) (active, N = 14; or sham, N = 14) over the left DLPFC, twice a day for three days with 1–2 days in between. Detailed neuropsychological assessment of five cognitive domains was performed before iTBS and on days 1, 10, and 30 after the last iTBS session. Composite Z-scores were calculated for each domain and for overall cognition. Results: Our results showed an increase in overall cognition up to one month in both groups but this effect was only significant in the active group. Improvements were seen in the attention domain for both groups and in the visuospatial domain in the active group only. No significant differences were found between the groups. Conclusion: These preliminary findings suggest that active iTBS might improve overall cognitive performance in patients with Parkinson's disease with mild cognitive impairment and that this effect can last up to one month. This cognitive improvement, is likely mediated by improvement on visuospatial abilities. Further studies are needed to explore the potential of iTBS as a therapeutical tool to slow cognitive decline in patients with Parkinson's disease. Highlights: Active TMS improves global cognitive performance over time in patients with Parkinson's disease and MCI. There is no significant difference between the active and sham TMS groups. Active and sham TMS improves attention but only active TMS improves visuospatial abilities. TMS has no effect on executive performance, language or memory. The potential sham TMS effect cannot be excluded.